THE IMPACT OF STATE SUBSIDY POLICY ON THE SUSTAINABLE DEVELOPMENT INDICATORS OF COMMERCIAL BANKS - Umurzакova Adiba Ochilovna (International Journal of Literature and Language Studies, 2026)
This paper examines how Uzbekistan’s state subsidy policies have influenced sustainable development outcomes in the banking sector over the last 5–10 years. We focus on social inclusion and SME finance, environmental and green-finance activity, and governance and risk management (ESG). Drawing on government policy documents and international reports (IMF, World Bank FSAP 2025, ADB), we synthesize evidence on directed and preferential credit, interest-compensation schemes, capital support, and concessional refinancing. Results indicate substantial gains in outreach—hundreds of thousands of borrowers supported—alongside growing momentum in green finance; however, recurring recapitalizations and pricing distortions reveal fiscal and governance trade-offs. The discussion outlines policy evolution toward more transparent, targeted, market-consistent instruments and the role of international partners in embedding ESG and accountability.